Harmonization of accounting in the process of globalization of economic activities - Floarea Georgescu; Cicilia Ionescu (Journal of Economic Development, Environment and People, 2014)
Abstract. Once with the Romania adhering at the European Union the public accounting system was transformed and adapted according to the requirements imposed by the international public sector accounting standards (IPSAS).This fact had imposed the appearance of legislative norms and provisions adapted to the actual requirements, by taking into account the growing and complex level of economic activities where the irreversible process of globalization takes place.